Influence of soil fertility on waterlogging tolerance of two Brachiaria grasses - Jiménez Serna, Juan de la Cruz; Cardoso Arango, Juan Andrés; Arango Londoño, David; Fischer, Gerhard; Rao, Idupulapati M. (Universidad Nacional de Colombia, 2015)
As a consequence of global warming, rainfall is expected to increase in several regions around the world. This, together with poor soil drainage, will result in waterlogged soil conditions. Brachiaria grasses are widely sown in the tropics and, these grasses confront seasonal waterlogged conditions. Several studies have indicated that an increase in nutrient availability could reduce the negative impact of waterlogging. Therefore, an outdoor study was conducted to evaluate the responses of two Brachiaria sp. grasses with contrasting tolerances to waterlogging, B. ruziziensis (sensitive) and B. humidicola (tolerant), with two soil fertility levels. The genotypes were grown with two different soil fertilization levels (high and low) and under well-drained or waterlogged soil conditions for 15 days. The biomass production, chlorophyll content, photosynthetic efficiency, and macro- (N, P, K, Ca, Mg and S) and micronutrient (Fe, Mn, Cu, Zn and B) contents in the shoot tissue were determined. Significant differences in the nutrient content of the genotypes and treatments were found. An increase of redoximorphic elements (Fe and Mn) in the soil solution occurred with the waterlogging. The greater tolerance of B. humidicola to waterlogged conditions might be due to an efficient root system that is able to acquire nutrients (N, P, K) and potentially exclude phytotoxic elements (Fe and Mn) under waterlogged conditions. A high nutrient availability in the waterlogged soils did not result in an improved tolerance for B. ruziziensis. The greater growth impairment seen in the B. ruziziensis with high soil fertility and waterlogging (as opposed to low soil fertility and waterlogging) was possibly due to an increased concentration of redoximorphic elements under these conditions.